The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1075/eurosla.7.08mas
|View full text |Cite
|
Sign up to set email alerts
|

When activity shapes the repertoire of second language learners

Abstract: Interactionists interested in second language acquisition postulate that learners’ competences are sensitive to the context in which they are put into play. Here we explore the language practices displayed, in a bilingual socio-educational milieu, by three dyads of English learners while carrying out oral communicative pair-work. In particular, we examine the role language choice plays in each task. A first analysis of our data indicates that the learners’ language choices seem to reveal the linguistic norms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
0
10
0
4
Order By: Relevance
“…Different studies of plurilingual interaction in learning environments have demonstrated how the mobilisation of students' whole plurilingual repertoires contributes positively to knowledge construction (e.g. Gajo, 2007;Masats, Nussbaum, & Unamuno, 2007;Moore, 2014;Nussbaum & Unamuno, 2000).…”
Section: Conversation Analysis Theory and Methodsmentioning
confidence: 99%
“…Different studies of plurilingual interaction in learning environments have demonstrated how the mobilisation of students' whole plurilingual repertoires contributes positively to knowledge construction (e.g. Gajo, 2007;Masats, Nussbaum, & Unamuno, 2007;Moore, 2014;Nussbaum & Unamuno, 2000).…”
Section: Conversation Analysis Theory and Methodsmentioning
confidence: 99%
“…More recently, Georges Lüdi and Bernard Py (2009) defined the bilingual individual as ''a free and active subject who has amassed a repertoire of resources and who activates this repertoire according to his/her need, knowledge or whims, modifying or combining them where necessary' ' (p. 159). From the perspective of language learning, research has further shown how, by using our entire language repertoires, we develop bilingualism and learn to participate in standard monolingual practices (Masats, Nussbaum and Unamuno 2007). Using entire language repertoires means doing things that bilinguals, such as the students in Ü nsal et al's data, do every day, including code-switching, translating and constructing hybrid words and structures.…”
Section: Linguistic Diversity and Educationmentioning
confidence: 99%
“…The transcription contains this information (observing and noting it) but as it is a fact that neither of the two participants in this exchange pick up on, we as researchers cannot categorize this deviation from the norm as a barrier in need of repair. Masats, Nussbaum, and Unamuno (2007) analyzed the problems that students come up against in a more general way, transcending the concept of repair, and categorized them according to the topics they fall under: the global format of the activity (what has to be done), the materials (as intermediary objects in the interaction), the global management of the task (how it should be managed), the resources available to the students in performing the task (if they have them available and/or consider them relevant to the local construction of the activity). In Fragment 5 we can observe some of these procedures that, unlike repairs, do not interrupt but rather maintain the conversational flow.…”
Section: The Concept Of Repairmentioning
confidence: 99%